1998
DOI: 10.1093/carcin/19.12.2151
|View full text |Cite
|
Sign up to set email alerts
|

Dietary genistein: perinatal mammary cancer prevention, bioavailability and toxicity testing in the rat

Abstract: Asian women consuming a traditional diet high in soy have a low incidence of breast cancer, yet when they emigrate to the USA the second but not the first generation lose this protection. Accordingly, we hypothesized that early exposure to genistein, a major component of soy, could have a permanent protective effect against breast cancer. Sprague-Dawley CD rats were exposed to genistein from conception to day 21 post-partum in the diet at concentrations of 0, 25 and 250 mg genistein/kg AIN-76A diet. At day 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
212
2
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(232 citation statements)
references
References 25 publications
12
212
2
6
Order By: Relevance
“…Studies examining whether an exposure to soy/SPI/genistein, which started at conception and continued until weaning, affects mammary tumorigenesis found a reduction in tumour multiplicity (Fritz et al, 1998; Table 1). Two groups have examined the effects of SPI exposure, which began during gestation and continued throughout adulthood on mammary tumorigenesis, reporting a reduction in mammary tumour incidence and/or multiplicity (Hakkak et al, 2000;Su et al, 2007a).…”
Section: Ratsmentioning
confidence: 99%
“…Studies examining whether an exposure to soy/SPI/genistein, which started at conception and continued until weaning, affects mammary tumorigenesis found a reduction in tumour multiplicity (Fritz et al, 1998; Table 1). Two groups have examined the effects of SPI exposure, which began during gestation and continued throughout adulthood on mammary tumorigenesis, reporting a reduction in mammary tumour incidence and/or multiplicity (Hakkak et al, 2000;Su et al, 2007a).…”
Section: Ratsmentioning
confidence: 99%
“…Furthermore, epidemiologic studies have detected an association between phytoestrogen consumption, phytoestrogen levels in plasma and urine, and reduced risk of breast cancer [28,36]. Studies using animal models of breast cancer have shown that a number of phytoestrogens, including quercetin, reduce the incidence and inhibit the development of N-methyl-N-nitrosourea (NMU) and DMBA-induced mammary carcinogenesis in rats [37][38][39][40][41][42][43]. Conversely, quercetin was shown to increase the severity of E2-induced kidney tumorigenesis in male Syrian hamsters [44].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Fritz et al reported that in the case of the rat dams fed 250 mg genistein/kg diet, genistein was detected at high concentrations in the milk of dams and in the stomach contents of suckling pups at PND 7 (137Ϯ34 pmol/mL and 4,439Ϯ1,109 pmol/mL), respectively (16). Although the secreted rates of genistein to dams' milk were different among the studies, the proportion of aglycone was high in the each study (16,25).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Fritz et al reported that in the case of the rat dams fed 250 mg genistein/kg diet, genistein was detected at high concentrations in the milk of dams and in the stomach contents of suckling pups at PND 7 (137Ϯ34 pmol/mL and 4,439Ϯ1,109 pmol/mL), respectively (16). Although the secreted rates of genistein to dams' milk were different among the studies, the proportion of aglycone was high in the each study (16,25). Although in the present experiment, the concentrations of genistein in the serum of nursing dams and dams' milk were not measured, it was confirmed from the previous reports (16,25) that genistein had transfered from the dams to suckling pups, and that the proportion of aglycone was high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation